Retro graphics : a visual sourcebook to 100 years of graphic design - Raimes, Jonathan; Bhaskaran, Lakshmi (San Francisco : Chronicle Books, 2007)
From the Publisher: Retro Graphics makes it easy for DIY designers to mimic the most prominent styles of the past hundred years. A plethora of authentic design models from Art Deco and Gothic Revival to Pop Art and Post Modernism are presented and broken down into their component parts in this handy sourcebook. These entries include step-by-step techniques, color palettes, typefaces, illustration styles, and ornamentation to help anyone create the look of such diverse materials as Victorian advertisements and pulp fiction book jackets. History can't be revived, but it can be simulated with this richly illustrated and meticulously researched visual encyclopedia.
boek